Characterization of CD8+ T-Cell Responses in the Peripheral Blood and Skin Injection Sites of Melanoma Patients Treated with mRNA Electroporated Autologous Dendritic Cells (TriMixDC-MEL). (3rd January 2013) - Benteyn, Daphné; Van Nuffel, An M. T.; Wilgenhof, Sofie; Corthals, Jurgen; Heirman, Carlo; Neyns, Bart; Thielemans, Kris; Bonehill, Aude
Abstract : Treatment of melanoma patients with mRNA electroporated dendritic cells (TriMixDC-MEL) stimulates T-cell responses against the presented tumor-associated antigens (TAAs). In the current clinical trials, melanoma patients with systemic metastases are treated, requiring priming and/or expansion of preexisting TAA-specific T cells that are able to migrate to both the skin and internal organs. We monitored the presence of TAA-specific CD8 + T cells infiltrating the skin at sites of intradermal TriMixDC-MEL injection (SKILs) and within the circulation of melanoma patients treated in two clinical trials. In 10 out of fourteen (71%) patients screened, CD8 + T cells recognizing any of the four TAA presented by TriMixDC-MEL cellular vaccine were found in both compartments. In total, 30 TAA-specific T-cell responses were detected among the SKILs and 29 among peripheral blood T cells, of which 24 in common. A detailed characterization of the antigen specificity of CD8 + T-cell populations in four patients indicates that the majority of the epitopes detected were only recognized by CD8 + T cells derived from either skin biopsies or peripheral blood, indicating that some compartmentalization occurs after TriMix-DC therapy. To conclude, functional TAA-specific CD8 + T cells distribute both to the skin and peripheral blood of patients after TriMixDC-MEL therapy.